PANDEMIC COVID-19, ECONOMIC PERFORMANCE, and SHARE MARKET PERFORMANCE (Case Study in Indonesia) - istiono, istiono; astawinetu, erwin dyah; handini, sri (Universitas Dr. Soetomo, 2021)
This research was conducted to determine and analyze the influence of the Covid-19 pandemic on economic performance and stock market performance in Indonesia.The influence analysis was carried out by means of the paired average test. For data that are normally distributed using the t-test and for data that are not normally distributed using the Wilcoxon sign test.This study finds that the Covid-19 pandemic has reduced economic performance and the performance of the Indonesian stock market.